Rethinking the subject in feminist research: narrative personae and stories of 'the real'. Issue 6 (3rd July 2018) - Tamboukou, Maria
ABSTRACT: In this paper, I discuss the question of 'the death of the subject' within feminist narratology and beyond. In doing this, I bring forward the notion of the 'narrative persona', a configuration that refers to the writing of feminist genealogies by drawing on women's auto/biographical narratives. The narrative personae of my inquiries emerge from Deleuze and Guattari's philosophy and Arendt's political thought: they are taken as conceptual and aesthetic figures, who narrate and act and whose stories create a scene for dialogic exchanges, communication, understanding, ethical responsibility and action. In fleshing out the concept of the narrative persona, I draw on my research with women workers' narratives particularly focusing on Désirée Véret-Gay, the seamstress who founded the first feminist newspaper La Femme Libre in nineteenth-century France. Her political writings in the form of letters, petitions and journal articles have become a significant body in the archives of feminist history. But although she lived a fully active political life she did not reveal much about her inner thoughts and passions, with the exception of a few letters that I will discuss in this paper entering into the dialogue of her epistolary discourse.